Efficient in vitro regeneration of Zingiber zerumbet Smith (a valuable medicinal plant) plantlets from rhizome bud explants - Qamaruz Zaman, Faridah; Abdelmageed, Adil Hassan Ahmed; Abd Aziz, Julia; R., Nor Hafizah (Academic Journals, 2011)
This study was conducted to develop an efficient protocol for mass propagation ofZingiber zerumbet Smith. Explants from rhizome buds were cultured on Murashige and Skoog (MS) medium supplemented with 6-Benzylaminopurine (BAP) alone (0 to 5 mg/l) or a combination of BAP (0 to 5 mg/l) and indole 3-acetic acid (IAA) (0 to 2 mg/l). MS medium supplemented with a combination of 5.0 mg/l BAP and 2.0 mg/l IAA or 3.0 mg/l BAP and 0.5 mg/l IAA produced the highest mean number of shoots (5.6) per explant as compared to other concentrations. The best shoots length (9.44 cm) was obtained on the medium containing 1.0 mg/l of BAP and 2.0 mg/l IAA. Thus, combined effects of BAP and IAA improved significantly the shoot growth and proliferation. MS medium supplemented with a combination of 5.0 mg/l BAP and 2 mg/l IAA gave the highest number of roots (17). However, longest roots per explant were obtained with 1.0 mg/l BAP alone. The proliferated shoots were green and healthy in appearance. Finally, healthy and complete plants with well developed roots were hardened, acclimatized and planted in the field successfully with a survival rate of 80%.